Structural and Parametric Optimization of Automatic Control System with Differentiation of Intermediate Signal - G. T. Kulakov; A. T. Kulakov; M. L. Korzun; D. V. Basalaj (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes to improve a standard automatic control double-circuit system while changing a differentiator by difference of complete and incomplete inertial area models of the regulated object and also by using a PID-regulator instead of a PI-regulator and a device for internal disturbance compensations. Methods for structural and parametric optimization of the main regulator and device for internal disturbance compensations that allow to improve the regulation process have been proposed in the paper.